The Effectiveness of a Psychological Counseling Program on Developing Future Optimism Among Students of the Department of Physical Education and Sports Sciences at Zakho University - Abdullah, Musab Mohammed; Omar, Jehan Hussein; Mohammed, Safad Mudhafar (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The current study aimed to identify the level of future optimism among students of the College of Education, specializing in Physical Education and Sports Sciences, and to determine the significance of differences based on certain demographic variables (gender, residence, marital status). Additionally, the study aimed to construct a psychological counseling program for the sample individuals. This research is quantitative. The study population included all fourth-year students of the morning session at the College of Education - Department of Physical Education and Sports Sciences at Zakho University, totaling 39 students. The sample was chosen purposively, representing 31% of the total population. Data collection techniques using questionnaires. Data analysis techniques using the Wilcoxon non-parametric test and the Mann-Whitney U test. The results indicated a low level of future optimism, with no significant differences observed in the sample attributed to demographic variables or the effectiveness of the psychological counseling program. Based on the findings, recommendations and suggestions were presented at the study's conclusion.